Ali Shogentsukov and the National Literary Process of the 20th Century (to the Axiology of Re-reading) - Yuri M. Tkhagazitov; Lyudmila B. Khavzhokova (Studia Litterarum)
The main purpose of the article is to study the organic combination of problemcontent and artistic-stylistic aspects in the further development of Shogentsukov’s traditions in Kabardian literature. To achieve this goal, it seems necessary to reveal the essence of national traditions and the artistic experience of Russian literature as the basis for the interdependence of “ours” and “theirs” in the formation of the artistic world of the founder and classic of Kabardian literature, Ali Askhadovich Shogentsukov (1900–1941). In accordance with the purpose and task of the study, the authors of the article propose a hypothesis that not only does Shogentsukov’s work belong to the history of national literature and its development, it is also a lively contribution to the modern national literature. The article overcomes a purely ideological interpretation of Ali Shogentsukov’s work and consolidates the idea of his role in the evolution of the national literary process.